Integrated systems improve the sustainability of soybean cultivation in the tropical region - e Silva, João Antônio Gonçalves; Costa, Kátia Aparecida de Pinho; da Silva, Luciana Maria; Severiano, Eduardo da Costa; Silva, Fabiano Guimarães; Habermann, Eduardo; Martinez, Carlos Alberto; Vilela, Lourival; da Silva, Alessandro Guerra; Costa, Adriano Carvalho; Costa, João Victor Campos Pinho; de Oliveira, Katryne Jordana (Frontiers in Sustainable Food Systems, 2023)
Inter-cropping between annual crops with tropical forages through integration crop-livestock systems (ICL) is considered a sustainable option to increase crop diversity and soybean productivity. In this study, we evaluated (1) the biomass production, desiccation efficiency, nutrient accumulation, and biomass decomposition of soil crop residues produced by Panicum maximum plants intercropped with maize in two different sowing methods during the second harvest and (2) investigated how soil crop residues impact the productivity of soybean. The experiment was conducted in a complete block design with three replicates. We compared conventional soybean cultivation with soybean cultivated over soil crop residues produced by a previous integration between maize and two Panicum maximum cultivars: Tamani and Zuri guinea grass, within and between rows of maize plants. Our results showed that Tamani guinea grass showed the highest desiccation efficiency. Zuri and Tamani guinea grass cultivated within and between maize plants resulted in higher biomass production and nutrient cycling potential, resulting in an increase of 28.4% in soybean productivity, compared to soybean grown without soil crop residues. We concluded that ICL system is an efficient method to increase the sustainability of soybean cultivation.